Development and applications of a collection of single copy gene-based cytogenetic DNA markers in garden asparagus - You, Chen; Wen, Ruidong; Zhang, Zhilong; Cheng, Guangqian; Zhang, Yulan; Li, Ning; Deng, Chuanliang; Li, Shufen; Gao, Wujun (Frontiers in Plant Science, 2022)
Garden asparagus (Asparagus officinalis, 2n = 2x = 20 chromosomes) is an important dioecious vegetable crop and a model species for studying sex chromosome formation and evolution. However, few molecular cytogenetic studies on garden asparagus have been reported because of its small metaphase chromosomes, the scarcity of distinguished cytogenetic markers, and the high content of repetitive sequences. In this study, a set of single copy genes free of repetitive sequences with sizes ranging from 4.3 kb to 8.2 kb were screened and used as probes for fluorescence in situ hybridization (FISH) to identify individual chromosomes of garden asparagus. The chromosome-specific signal distribution patterns of these probes enabled the distinguishment of each pair of chromosomes. The sequence assembly and cytogenetic map were successfully integrated, and the results confirmed that the chromosome 1 representing the sex chromosome in the genome assembly is chromosome 5 in the karyotype analysis. The cytogenetic identification of the male-specific region of the Y chromosome (MSY) was implemented using a mixed probe derived from a number of MSY-specific single copy sequences. In addition, the chromosome orthologous relationship between garden asparagus (A1–A10, karyotypic analysis) and its hermaphrodite close relative, A. setaceus (B1–B10, karyotypic analysis), was analyzed using this collection of chromosome-specific cytological markers. The results showed that B3 is the ortholog of sex chromosome A5 and thus may represent the ancestral autosome of the current sex chromosome in garden asparagus. Chromosomes B5, B4, B1, B8, B7, and B9 are the orthologs of A2, A3, A4, A7, A8, and A10, respectively. The chromosome identification, cytogenetic recognition of MSY, and the orthologous relationship analysis between garden asparagus and A. setaceus are valuable for the further investigation of the sex chromosome emergence and evolutionary mechanism of garden asparagus and genome structure evolution in the Asparagus genus.